Comparision of Extramucosal Enucleation and Submucosal Excision Technique for the Treatment of Oral Mucocele at Birat Medical College & Teaching Hospital, Morang, Nepal - Shah, Rajeev Kumar; Sharma, VA; Atreya, A; Gyawali, S (Birat Journal of Health Sciences, 2017)
Introduction Mucocele is a painless swelling in the oral cavity usually conﬁned to the lower lip. Of the various treatment techniques surgery remains the best modality. Objectives The present study is aimed to observe the prevalence of mucocele in Eastern Region of Nepal and to compare the results of extramucosal enucleation and submucosal excision as the treatment of mucocele. Methodology This prospective study was conducted on patients diagnosed with mucocele in Birat Medical College Teaching Hospital; a tertiary centre in Eastern Nepal during the period between June 2014 to April 2017. Out of total 37 cases two groups were divided based upon size of mucocele. Patients underwent extramucosal enucleation in cases where the size of mucocele was less than 1 cm and submucosal excision was done in patients whose size of the mucocele exceeded 1 cm. The data was entered and analyzed using Statistical Package for the Social Sciences (SPSS) vs 21. Diﬀerent parameters like wound infection, scar formation, recurrence, healing time, follow up were compared for both the methods. Result The mean age of the patient in extramucosal enucleation was 9.90±2.807 while in submucosal excision was 11.22±3.068 years. The most common location for mucocele in both the groups was the lower lip; who underwent either extramucosal enucleation (90%) or submucosal excision (70.4%). Recurrence was not observed in submucosal excision whereas one patient with extramucosal enucleation had recurrence. Conclusion Mucocele in comparison to extramucosal enucleation as it usually healed within a week with fewer incidences of wound infection and without any recurrence. Birat Journal of Health Sciences Vol.2/No.1/Issue 2/ Jan - April 2017, Page: 215-218